Molecular Characterization of Pineapple (Ananas comosus L, Merr.) using Microsatellite Markers - Sri Rama Sari; Andini Hanif; Shahril Ab Razak; Nurul Shamimi Abdul Ghani (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The molecular characterization of pineapple germplasm (Ananas comosus L. Merr.) is crucial for evaluatinggenetic variation and supporting conservation and breeding initiatives. A total of 25 pineapple accessions wereused in this study. The accessions included cultivated types designated with the code (MP) and ornamental typesdesignated with the code (OC). Pineapple accessions were characterized using six simple sequence repeat (SSR)markers. These SSR markers revealed moderate levels of polymorphism, with the number of alleles per locusranging from 2 to 6, an average gene diversity of 0.63, and polymorphic information content (PIC) values rangingfrom 0.37 to 0.65. Pairwise genetic distances ranged from 0.000 to 0.917, reflecting a broad spectrum ofdivergence among the accessions. The UPGMA dendrogram grouped all accessions into two main clusters, with oneornamental accession (OC11) forming a distinct cluster, while the other ornamental and cultivated types wereintermixed, indicating partial genetic separation rather than complete divergence. The moderate number ofmarkers and the limited number of loci constrained the clustering resolution. The strength of this study lies in theavailability of genetic distance and clustering information, which can be used to identify the most divergentaccessions as candidate parents for crossing and to recognize highly related accessions to avoid collectionredundancy. It is recommended that accessions originating from different clusters and exhibiting high geneticdistances be prioritized as sources of genetic diversity in breeding programs. Additionally, increasing the numberof polymorphic SSR markers is advised to improve identification accuracy and clustering resolution.